BreakOut: predicting and breaking sedentary behaviour at work - Ferreira, Maria José; Karapanos, Evangelos; Caraban, Ana (My University, 2014)
We present BreakOut, a desktop system that infers an individual's posture, stress levels, and engagement with computer related tasks with the goal of recommending a break of sedentary behaviour at appropriate times. We present an Experience Sampling study that attempted to evaluate BreakOut's ability to infer users' posture and stress from a single webcamera as well as their engagement from keyboard and mouse activity. We conclude with the description of an ambient artistic display as well as an intuitive gestural interaction technique that enables the user to interact with BreakOut with minimal cognitive resources.
Keywords: Break; Engagement; Need for a break; Posture; Sedentary behaviour; Stress